Monitoring of coagulation factor therapy in patients with von Willebrand disease type 3 using a microchip flow chamber system - Ågren, Anna; Holmström, Margareta; Schmidt, David E.; Hosokawa, Kazuya; Blombäck, Margareta; Hjemdahl, Paul (Thrombosis and Haemostasis, 2017)
Patients with type 3 von Willebrand disease (VWD-3) have no measurable levels of VW factor (VWF) and usually require treatment with VWF-FVIII concentrate to prevent and/or stop bleeding. Even though the patients are treated prophylactically, they may experience bleeding symptoms. The aim of this study was to evaluate the effect of VWF-FVIII concentrate treatment in VWD-3 patients with the Total Thrombus Analysis System (T-TAS®), which measures thrombus formation under flow conditions. Coagulation profiles of 10 VWD-3 patients were analysed using T-TAS before and 30 minutes after VWF-FVIII concentrate (Haemate®) injection. Results were compared to VWF- and FVIII activity in plasma, and results with thromboelastometry and ris-tocetin-activated platelet impedance aggregometry (Multiplate®) in whole blood. For comparison, 10 healthy controls were also analysed with T-TAS. A median dose of 27 (range 15–35) IU/kg of VWF-FVIII concentrate increased VWF- and FVIII activity as expected. T-TAS thrombus formation was enhanced when a tissue factor/collagen-coated flow chamber was used at low shear, but treatment effects at high shear using a collagen-coated flow chamber were minimal. Whole blood coagulation assessed by thromboelastometry was normal and did not change (p > 0.05) but ristocetin-induced platelet aggregation improved (p < 0.001). In conclusion, T-TAS detects effects of VWF-FVIII concentrate treatment on coagulation-dependent thrombus formation at low shear, but minor effects are observed on platelet-dependent thrombus formation at high shear. The poor prediction of bleeding by conventional laboratory monitoring in VWD-3 patients might be related to insufficient restoration of platelet-dependent thrombus formation.
Keywords: Coagulation tests; flow chamber system; thromboelastography; von Willebrand disease; von Willebrand factor